The combined use of conventional MRI and MR spectroscopic imaging increases the diagnostic accuracy in amyotrophic lateral sclerosis. Issue 1 (January 2015) - Cervo, Amedeo; Cocozza, Sirio; Saccà, Francesco; Giorgio, Sara M.d.A.; Morra, Vincenzo Brescia; Tedeschi, Enrico; Marsili, Angela; Vacca, Giovanni; Palma, Vincenzo; Brunetti, Arturo; Quarantelli, Mario
Highlights: We assessed in ALS the diagnostic accuracy of MRI signal and MRS data used alone and in combination. We found that T2-hypointensity and NAA decrease in motor cortex are two independent phenomena. These two variables taken alone do not provide acceptable diagnostic accuracy in ALS. The same variables, when used in combination, improve the diagnostic accuracy of MRI in ALS. Abstract: Purpose: We aimed to assess, in amyotrophic lateral sclerosis (ALS), the diagnostic accuracy of the combined use of conventional MRI signal changes (namely, hypointensity of the precentral cortex and hyperintensity of the corticospinal tracts on T2-weighted images), and N-Acetyl-Aspartate (NAA) reduction in the motor cortex at Magnetic Resonance Spectroscopy (MRS), which are affected by limited diagnostic accuracy when used separately. Methods: T2-hypointensity and NAA/(Choline + Creatine) ratio of the precentral gyrus and T2-hyperintensity of the corticospinal tracts were measured in 84 ALS patients and 28 healthy controls, using a Region-of-Interest approach. Sensitivity and specificity values were calculated using Fisher stepwise discriminant analysis, and cross-validated using the leave-one-out method. Results: Precentral gyrus T2 signal intensity ( p  < 10 −4 ) and NAA peak ( p  < 10 −6 ) were significantly reduced in patients, and their values did not correlate significantly to each other both in patients and controls, while no significant differences were obtained in terms of T2-hyperintensity of the corticospinal tract. Sensitivity and specificity of the two discriminant variables, taken alone, were 71.4% and 75.0%, for NAA peak, and 63.1% and 71.4% for T2-hypointensity, respectively. When using these two variables in combination, a significant increase in sensitivity (78.6%) and specificity (82.1%) was achieved. Conclusions: Precentral gyrus T2-hypointensity and NAA peak are not significantly correlated in ALS patients, suggesting that they reflect relatively independent phenomena. The combined use of these measures improves the diagnostic accuracy of MRI in ALS diagnosis.